2014
DOI: 10.1371/journal.pone.0088174
|View full text |Cite
|
Sign up to set email alerts
|

TLR2, TLR4 and CD14 Recognize Venom-Associated Molecular Patterns from Tityus serrulatus to Induce Macrophage-Derived Inflammatory Mediators

Abstract: Scorpion sting-induced human envenomation provokes an intense inflammatory reaction. However, the mechanisms behind the recognition of scorpion venom and the induction of mediator release in mammalian cells are unknown. We demonstrated that TLR2, TLR4 and CD14 receptors sense Tityus serrulatus venom (TsV) and its major component, toxin 1 (Ts1), to mediate cytokine and lipid mediator production. Additionally, we demonstrated that TsV induces TLR2- and TLR4/MyD88-dependent NF-κB activation and TLR4-dependent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 71 publications
1
60
0
16
Order By: Relevance
“…This interaction recruits myeloid differentiation factor (MyD88) and activates the activator protein 1(AP-1) and NF-kB pathways. Similarly, Ts1 induces TNF-a and IL-6 production in a manner that is dependent on TLR2, TLR4 and CD14, although signaling occurs mainly through NF-kB activation (Zoccal et al, 2014).…”
Section: Immuno-modulatorsmentioning
confidence: 99%
“…This interaction recruits myeloid differentiation factor (MyD88) and activates the activator protein 1(AP-1) and NF-kB pathways. Similarly, Ts1 induces TNF-a and IL-6 production in a manner that is dependent on TLR2, TLR4 and CD14, although signaling occurs mainly through NF-kB activation (Zoccal et al, 2014).…”
Section: Immuno-modulatorsmentioning
confidence: 99%
“…Recently, Zoccal et al (2014) revealed that Ts venom and the major toxin Ts1 can induce the production of inflammatory mediators by interacting with TLR2 and CD14/TLR4, which confirmed that these toxins can target receptors different from sodium channels as well as a different pathway [16].…”
Section: Discussionmentioning
confidence: 96%
“…After pattern recognition by PRRs, macrophages activate an immune response that can result in the production of pro-inflammatory cytokines [38]. Recently, the term venom-associated molecular pattern (VAMP) was proposed to refer to molecules from venoms that can be recognized by PRRs [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Tityus serrulatus (TSV) venom stimulated the release of NO in the presence of LPS in the murine macrophage cell line [11]. Another study by the same group showed that TSV venom induces a typical M1 profile through the recognition of TSV by TLR2 and TLR4, resulting in NF-kB activation to generate IL-6 and TNF-a [12]. TSV Venom is recognized by pattern recognition receptors such us TLR2 and TLR4, although recent evidence shows that bee venom can also be recognized by TLR4-independent mechanisms leading to inflammasome activation [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the toxic components from Tityus serrulatus (TSV) venom stimulated the release of NO in the presence of LPS in the murine macrophage cell line [11]. Another study by the same group showed that TSV venom induces a typical M1 profile through the recognition of TSV by TLR2 and TLR4 [12]. The common response of macrophages to scorpion venoms mainly involves the upregulation of genes involved in M1 phenotype, including cytokines likes IL6, TNF-a, and NOSi.…”
Section: Introductionmentioning
confidence: 99%